Indoor Air Pollution (IAP) Traceable to Household Fuel Consumption and its Impact on Health - Shakya, S.; Choosong, T.; Techato, K.; Gyawali, S.; Panthee, B.; Shrestha, N.; Dangal, M.R. (Kathmandu University Medical Journal, 2021)
Energy is an essential and obligatory prerequisite of life. Indoor air pollution is one of the biggest environmental problems in the world being specifically concentrated in resource limited settings. Inspite of the availability of cleaner fuel technologies, people in resource limited setting still depend on traditional fuel to meet their basic needs resulting even in premature deaths. In Nepal people in rural areas are the pre-dominant users of biomass fuel, there is limited research focusing on rural areas particularly; women as they spend most of their time in kitchen. Reports were extensively searched for literature using preset keywords in English language peer-reviewed journals databases PubMed and Google Scholar published between the years 2005 to 2020. Citation details were examined, titles and abstracts screened for eligibility and if relevant, full text was also reviewed in greater detail. Findings were then presented primarily under two bold themes: Household fuel consumption: existing theories and evidence; and health impact of indoor air pollution. Several health effects were reported of indoor air pollution including respiratory illnesses, cardiovascular diseases, cancer, endocrine system disruption and pregnancy complications. These exposures almost double the health risks predominantly among children and women of rural communities as they are directly involved in household activities causing air pollution. Based on our review of evidence, women and children of rural households were the major victims. Further, determinants of household fuel consumption and health effects should be considered while formulating policies in regard to promoting accessibility of clean fuels and reducing household air pollutants.